2016
DOI: 10.1093/jisesa/iew015
|View full text |Cite
|
Sign up to set email alerts
|

Identification and Characterization of Two “Sensory Neuron Membrane Proteins” (SNMPs) of the Desert Locust,Schistocerca gregaria(Orthoptera: Acrididae)

Abstract: Pheromone-responsive neurons of insects not only require specific receptors but in addition several auxiliary components, including the “sensory neuron membrane protein,” SNMP. Accordingly, SNMP is considered as a marker for neurons responding to pheromones. For the desert locust Schistocerca gregaria, it is known that the behavior, including aggregation behavior and courtship inhibition, is largely controlled by pheromones. However, little is known about pheromones, their receptors, and the pheromone-responsi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
57
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 52 publications
(63 citation statements)
references
References 53 publications
(79 reference statements)
4
57
0
Order By: Relevance
“…Generally, SNMP1s are distributed in different types of sensilla. In S. gregaria , S. litura , A. ipsilon , H. virescens and A. polyphemus , SNMP1s are commonly expressed in pheromone‐sensitive sensilla (trichodea and basiconica) (Rogers et al ., , ; Forstner et al ., ; Gu et al ., ; Zhang et al ., ; Jiang et al ., ). In Drosophila , SNMP1 mainly concentrated in the trichoid sensory cilia of antennae, is essential for detecting sex‐pheromone cVA (Benton et al ., ; Jin et al ., ).…”
Section: Discussionmentioning
confidence: 97%
“…Generally, SNMP1s are distributed in different types of sensilla. In S. gregaria , S. litura , A. ipsilon , H. virescens and A. polyphemus , SNMP1s are commonly expressed in pheromone‐sensitive sensilla (trichodea and basiconica) (Rogers et al ., , ; Forstner et al ., ; Gu et al ., ; Zhang et al ., ; Jiang et al ., ). In Drosophila , SNMP1 mainly concentrated in the trichoid sensory cilia of antennae, is essential for detecting sex‐pheromone cVA (Benton et al ., ; Jin et al ., ).…”
Section: Discussionmentioning
confidence: 97%
“…Insect SNMPs are two transmembrane domain-containing proteins in olfactory neurons of antennae and localized in dendrite membranes. They were first identified in the pheromone-sensitive hairs of the wild silk moth Antheraea polyphemus [87] and tobacco hornmoth Manduca sexta [88,89], and now are described in various insect orders namely including Lepidoptera, Coleoptera, Hymenoptera and Diptera [90] and recently Orthoptera [91]. Several functions of insect SNMPs in odorant detection have been predicted (reviewed in [90]) including interactions with pheromone binding protein (PBP)-pheromone complexes, OBP/odorant complexes, OR proteins.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, a recent study provided strong evidence that OBPs and ORs in the palps are involved in detecting specific odours during the feeding process of locust (Li et al , ). The recent discovery that SNMP1, a marker for pheromone‐sensitive neurons, is also expressed in the palps points to the possibility that some OSNs in the palps may even be responsive for pheromones (Jiang et al , .…”
Section: Discussionmentioning
confidence: 99%
“…In fact, a recent study provided strong evidence that OBPs and ORs in the palps are involved in detecting specific odours during the feeding process of locust (Li et al, 2018). The recent discovery that SNMP1, a marker for pheromone-sensitive neurons, is also expressed in the palps points to the possibility that some OSNs in the palps may even be responsive for pheromones (Jiang et al, 2016. Double labelling experiments have shown that OBP1 and OBP5, members of the OBP subfamily I-A, were expressed in a low number of cell clusters and in close proximity to Orco-positive cells (Figs 3 and 4). This result implies that OBP1 and OBP5 are expressed in sensilla types housing OSNs, similar to the expression pattern found on the antennae .…”
Section: Discussionmentioning
confidence: 99%